Mechanical Features of PMMA Microfluidic Chips Implemented by Carbon Dioxide Laser - Hussein, Noor luay; Mahdi, Zainab F. (Iraqi Journal of Science, 2024)
An experimental investigation of the laser engraved process is carried out on.2.5 mm.thick acrylic Polymethyl Methacrylate (PMMA).using Carbon Dioxide,(CO2) laser. PMMA is a typical polymer.suitable for manufacturing microfluidic chips (Y shape). Fabrication parameters have an influence on the mechanical properties of the manufactured components. The effects of laser power (20, 40, and 60 W) and scanning speed (250, 350, and 500 mm /s) were evaluated on the microstructure and mechanical characteristics of microfluidic chips. With an increase in laser power and a decrease in scanning speed, the stacking of melt pools became more organized, pores were less visible, and mechanical characteristics improved. At a power density of 60 W and a speed of 250 mm/s, the best mechanical parameters were obtained, including a yield strength of 20.72 MPa, an ultimate tensile strength of 30.81 MPa, and an elongation of 1.163 percent. For the same laser energy density, however, change in laser power has a greater influence on the pore defect than variation in scanning speed.